An Intelligent Evaluation Method of Supply-Demand Matching Degree Based on ELECTRE III and VIKOR in Cloud Manufacturing Platform - Jihong Pang; Yuxuan Shi; Jinkun Dai (IEEE Access)
Supply-demand matching degree evaluation is an effective way to reduce the transaction risk of manufacturing supply-demand subjects. Cloud manufacturing provides a platform for supply-demand entities through the network. Based on the characteristics of cloud manufacturing, this paper proposes an intelligent evaluation method of supply-demand matching degree based on ELECTRE III and VIKOR. Firstly, the demand side uploads a bill of material on the cloud manufacturing platform, and the supplier provides a supply plan. The demand side forms an evaluation team to evaluate the quality of the supplied product. Secondly, the weight of the evaluators is calculated in cloud manufacturing platform based on the similarity measurement method. Then, the cloud manufacturing platform carries out the weighted aggregation of evaluation information and uses the ELECTRE III method to build the weak advantage relationship among indicators. Finally, the cloud manufacturing platform performs a VIKOR compromise calculation and selects the optimal supply-demand matching degree. At the end of the paper, an example is taken to evaluate the matching degree of supply-demand of robot machined parts, to demonstrate the practicability of the new method. Based on Canny algorithm, a robot action stability test platform is built to verify the calculation results of the new method.